PELATIHAN PENERAPAN LABEL PANGAN SESUAI KETENTUAN DAN LEGALITAS USAHA HALAL BAGI UMKM PANGAN DI DESA PAGARUYUNG, KABUPATEN KAMPAR PROVINSI RIAU - Riftyan, Emma; Yusmarini, Yusmarini; Siregar, Erpiani; Dewi, Yossie Kharisma; Shanti Fitriani; Ayu, Dewi; Maulida, Yusni; Pato, Usman (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
Pagaruyung Village in Kampar Regency is one of the largest pineapple-producing centers in Riau Province and is being developed as a pineapple-based food processing center. However, the increase in the number of foodMSMEs in this village has not been accompanied by adequate understanding regarding the application of food labels according to BPOM regulations and the fulfillment of halal business legality required by BPJPH. This community service activity aimed to increase the knowledge of MSME actors regarding proper and correct food labeling, as well as the application of MSME halal business legality. This training was held on October 11, 2025, and was attended by 17 participants. The implementation methods used for this service activity include a pretest, material presentation, mentoring, discussion, and a final evaluation in the form of a posttest. The evaluation results showed a significant improvement in participants' understanding, with a 98% presentation rate regarding the proper and correct application of food labels and halal certification for MSMEs. This activity makes an important contribution to increasing the readiness of Pagaruyung Village MSMEs to produce pineapple products that are safe, of high quality, and meet food legality standards.